Making a New Deal: Industrial Workers in Chicago, 1919-1939 - Barrett, James R. (Labour / Le Travail, 1992)
The article reviews the book, "Making a New Deal: Industrial Workers in Chicago, 1919-1939," by Lizabeth Cohen.
Keywords: BOOKS -- Reviews; COHEN, Lizabeth; INDUSTRIAL workers; MAKING a New Deal: Industrial Workers in Chicago 1919-1939 (Book); Nonfiction